2020
DOI: 10.3390/en13092281
|View full text |Cite
|
Sign up to set email alerts
|

Phasing out Energy Subsidies to Improve Energy Mix: A Dead End

Abstract: A major energy transformation is required to prolong the rise in global temperature below 2 °C. The Indonesian government (GoI) has set a strategy to gradually remove fuel subsidies to meet its 2050 ambitious energy targets. Using a recursive dynamic computable general equilibrium (CGE) model, the present study aimed to determine whether or not the current energy subsidy reforms would meet the targets of both energy mix and energy intensity. It also incorporated the environmental aspect while developing a sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…According to these suggestions, the swap concept recommends that the government reallocate fossil energy subsidies to clean energy investments to expand economic growth; however, the results from reallocations vary by the area of study. An Indonesian study reported that eliminating energy subsidies and transferring money to invest in infrastructure and the renewable energy industry would positively impact the economy [21]. As shown by a study in South Africa, a decrease in the fuel subsidy and reallocating budgets to support public transportation would positively impact the economy [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to these suggestions, the swap concept recommends that the government reallocate fossil energy subsidies to clean energy investments to expand economic growth; however, the results from reallocations vary by the area of study. An Indonesian study reported that eliminating energy subsidies and transferring money to invest in infrastructure and the renewable energy industry would positively impact the economy [21]. As shown by a study in South Africa, a decrease in the fuel subsidy and reallocating budgets to support public transportation would positively impact the economy [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…An additional analysis of subsidies for energy efficiency improvement measures has shown that the elimination of artificial price reductions alone is not enough to achieve long-term energy efficiency goals [35]. In many countries, subsidies for innovative energy performance measures, in particular those using renewable energy, are used to increase the energy efficiency of a building [36].…”
Section: Resultsmentioning
confidence: 99%
“… Country Eligible Sectors RE Capacity Cap RE Target Tariffs for Surplus Energy fed into the Grid [ 37 , 43 ] [ 97 , 98 ] Thailand commercial, industrial, residential Up to 1MWp Renewable energy will make up 22% of overall power output and 32% of energy demand by 2036. THB 9.0–12.0 per kWh for net metering; THB 3.0–4.5 cents per kWh for net billing [ 96 ] [ 67 , 98 ] [ 99 , 100 ] Philippines Residential, commercial, industrial, institutional Up to 100kWp 100% by 2050 (20GW by 2040) Tariff for net metering (fixed tariff): 10.89 Philippine peso cents per kWh (excess energy is credited to the following month's electricity bill) [ 96 ] [ 83 , 101 , 102 ] Indonesia Commercial, residential, industrial The annual energy usage of qualified users should not exceed the generation from DG systems. 26% of installed capacity by 2025 Tariff for net metering: 11–13 Indonesian rupiah cents per kWh (net metering is not on a 1:1 basis; the excess energy is fed into the Grid at 65% of the applicable tariff) [ 96 ] [ 63 , 103 , 104 ] Vietnam Residential sector No capacity limit is imposed By 2020, 2030, and 2050, renewable energy will account for 7%, 10%, and 100% of total electricity generation, respectively.…”
Section: Energy Policies In Southeast Asian Countriesmentioning
confidence: 99%